2013
DOI: 10.1111/joa.12087
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the anterolateral ligament of the knee

Abstract: In 1879, the French surgeon Segond described the existence of a 'pearly, resistant, fibrous band' at the anterolateral aspect of the human knee, attached to the eponymous Segond fracture. To date, the enigma surrounding this anatomical structure is reflected in confusing names such as '(mid-third) lateral capsular ligament', 'capsulo-osseous layer of the iliotibial band' or 'anterolateral ligament', and no clear anatomical description has yet been provided. In this study, the presence and characteristics of Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

62
1,031
7
60

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 731 publications
(1,171 citation statements)
references
References 24 publications
62
1,031
7
60
Order By: Relevance
“…The more anatomic double-bundle ACL reconstruction was proposed to overcome potential rotatory instability of the knee, but consensus has not been reached regarding its widespread use [26,27,44]. In addition, studies have shown that the posterolateral bundle contributes little to rotational stability of the knee; this function might be performed by peripheral structures such as the anterolateral ligament [8,28,45].…”
Section: Introductionmentioning
confidence: 99%
“…The more anatomic double-bundle ACL reconstruction was proposed to overcome potential rotatory instability of the knee, but consensus has not been reached regarding its widespread use [26,27,44]. In addition, studies have shown that the posterolateral bundle contributes little to rotational stability of the knee; this function might be performed by peripheral structures such as the anterolateral ligament [8,28,45].…”
Section: Introductionmentioning
confidence: 99%
“…8,9,22 Recently, Kittl et al 10 performed a biomechanical analysis of 8 cadaveric knees and measured the length changes of several combinations of tibiofemoral points (including several previously performed ALES reconstructions) at knee flexion angles between 0 and 90 . Their results suggested that graft placement proximal to the lateral femoral epicondyle tunneled deep to the LCL and connecting to the Gerdy tubercle was the most isometric.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,13 Although some authors have named the identified structure the "anterolateral ligament," inconsistency on the femoral attachment site is seen. [8][9][10][11] The tibial attachment site is consistently described to be halfway between the tip of the fibular head and the center of the Gerdy tubercle. Discrepancies exist on the association or attachment to the lateral meniscus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the understanding of the anterolateral structures as a restraint, recent publications of a newly discovered "anterior longitudinal ligament" has engaged the research community in a re-examination of the anatomical, histological, and biomechanical components of the anterolateral capsule [59,60]. Recent anatomic study has reported the dissections of 24 different animal species in which a double lateral collateral ligament (LCL) was observed in three types of primates, but no discrete ALL was ever discovered.…”
Section: Anatomical and Biomechanical Implications Of The Anterolatermentioning
confidence: 99%